Toward a social construction of water resources management: The case of Kalimantan. Issue 1 (1st January 2021) - Sriyono, Edy; Asri, Dyah Permata Budi; Sardi, Sardi
Abstract: Water resource management in the era of disruptive innovation and industrial revolution 4.0 is becoming more complex and challenging. The aim of this article is to criticize the current development of water resources which often neglects the social construction of its artefacts. We argue that such disentanglement has become the main driver of more severe social problems, economic inequality, sustainability issues, among others. This research uses Anthony Giddens structuration theory which looks at the relationship between agents and structures with an epistemological approach to clarify the underlying reasons. We combined the use of participant-observation as well as a desk study to examine the relation of social aspects in the context of water management by following the qualitative ethnographic approach that allows us to "be there". Data collection was carried out through observation and secondary documentation. The integration between poiesis and praxis is an important factor towards a more balanced water management practice. Departing from structuration theory and social construction perspective, we found that there is a separation in the management of water resources. We then propose a model for developing a more balanced water resource management by taking into account social construction in its surrounding environment. Therefore, it is important for academics, policymakers, and governments to manage water resources in a more multidimensional manner.